A Rare Case of Intraoperative Hypotension in Neurosurgical Setting: Diagnosis and Management of Transfusion-Associated Hypotension - Kambaduru, Pradeep; Hrishi, Ajay P.; Sreekumar, Sreeja; Rajendran, Vinu; Sreekumar, Sravan (Journal of Neuroanaesthesiology and Critical Care, 2025)
Transfusion-associated hypotension (TAH) is a rare but potentially serious complication characterized by a sudden onset of hypotension during or shortly after the initiation of a blood transfusion. Once other causes have been excluded, the hypotension resolves upon cessation of the transfusion. We report the case of a 49-year-old female scheduled for excision of a central neurocytoma via an interhemispheric approach. Intraoperatively, the patient developed unexplained hypotension unresponsive to inotropic support during tumor resection. After systematic exclusion of other differential diagnoses, TAH was considered as the most likely cause. Discontinuation of the transfusion led to the resolution of hypotension, confirming the diagnosis. This case highlights the importance of considering TAH as a differential diagnosis for intraoperative hypotension, particularly when unresponsive to standard management and temporally associated with transfusion. Prompt recognition and appropriate management are crucial to avoid unnecessary interventions and improve patient outcomes.
Keywords: intraoperative hypotension; blood transfusion; transfusion-associated hypotension